Oltre la Bibbia. Il cinema tra narrazione e redenzione (Altre Modernità, 2011)
In the Jewish tradition, the Bible is the origin of any possible interpretative and narrative development. Thus, starting from this statement and in the belief that film is, in its essence, narration and not representation, the author makes some remarks on the close and intimate relationship among Judaism, Jews and film, but also on the difficulty that movies have always experienced in the direct confrontation with the Bible while pretending to “represent it”. Moreover, if the cinema is mainly narrative and creative development of reality, we have to speak, with Walter Benjamin and Sigfried Kracauer, as for the Seventh art, about a sort of redemption of reality, in assonance, here again, with some profound and important trends of Judaism, and especially of the modern Jewish thought.
Keywords: Bibbia; narrazione; rappresentazione; cinema; redenzione.